Cardiovascular Disease Risk Factors in Diabetics with and without Metabolic Syndrome in NAFLD Patients - Alam, Mohammad Shane; Mjery, Yahia; Ahmad, Kamal; Kaabi, Yahia Ali; Akhter, Mohammad Suhail; Jabeen, Fakhra; Moshi, Jobran Mohammad; Alhazmi, Alaa Ali; Haque, Md Intekhabul; Abdalla, Saif Elden Babikar; Hazem, Mathkour (International Journal of Pharmaceutical Investigation, 2026)
Background Globally, Non-Alcoholic Fatty Liver Diseases (NAFLD) is considered as the frequent chronic liver diseases strongly linked with metabolic dysfunction and cardiovascular risk specifically in Type 2 Diabetes Mellitus (T2DM) cases. Metabolic Syndrome (Mets) is generally characterized by various cardiometabolic risk factors that frequently coexist with NAFLD, which elevates the chances of cardiovascular diseases (CVDs). This research aims to evaluate and compare CVD predictive factors in diabetic NAFLD individuals with or without Mets and to assess how clinical and biochemical profiles differ across different groups and fatty liver disease grades. Materials and Methods Observational cross-sectional single-centric research was performed over 12 months in the Department of Medicine. A total of 120 diabetic patients with NAFLD were enrolled and stratified into two different groups based on the presence (n=61) and absence (n=59) of metabolic syndrome. Demographic data, anthropometric measurements, and clinical and biochemical parameters of all enrolled participants were evaluated and comparatively analyzed. Statistical comparisons were carried out using independent sample t-tests and chi-square tests. Results Insignificant variations were observed in the age, gender, and BMI distribution of patients in any group. However, HDL cholesterol showed a significant reduction (p=0.025) and serum ALT revealed a significant increase in Mets patients than in patients not having Mets (p=0.020). Other clinical and biochemical parameters demonstrated insignificant distribution between diabetic NAFLD individuals having Mets or those without Mets. Furthermore, the severity of FLD does not have a notable influence on most cardiovascular risk variables. Conclusion Diabetic NAFLD patients with metabolic syndrome demonstrated unfavorable lipid profiles and higher levels of liver enzymes, which emphasize increased cardiovascular risk. Presence of Mets in diabetic NAFLD individuals underlines the urgency of early detection and targeted intervention to alleviate the risk of cardiovascular morbidity.
Keywords: Cardiovascular Disease Risk; Metabolic Syndrome; Non-alcoholic Fatty Liver Disease; Type 2 Diabetes Mellitus.